2012
DOI: 10.1088/0022-3727/45/47/475001
|View full text |Cite
|
Sign up to set email alerts
|

Disorder and weak localization effects in Co2MnxTi1−xAl Heusler alloy thin films

Abstract: The effects of disorder on the structural, magnetic and transport properties of stoichiometric Co2Mn x Ti1−x Al (0 ⩽ x ⩽ 1) thin films are reported. All the compositions exhibited B2-type structure with the actual composition of each film, as determined by Rutherford backscattering spectroscopy (RBS), being close to the nominal value. The values of saturation magnetization increase with increasing Mn content in the films and are in general agreement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Then with the improvement of crystallinity and structure ordering, weak localization reduces and eventually disappears at high preparing/annealing temperature. A similar upturn in resistivity ascribed to the weak localization has also been reported on Heusler alloys, such as Ni 2 MnGe [41] and Co 2 Mn x Ti 1-x Al [42].…”
Section: Transport Propertiessupporting
confidence: 79%
“…Then with the improvement of crystallinity and structure ordering, weak localization reduces and eventually disappears at high preparing/annealing temperature. A similar upturn in resistivity ascribed to the weak localization has also been reported on Heusler alloys, such as Ni 2 MnGe [41] and Co 2 Mn x Ti 1-x Al [42].…”
Section: Transport Propertiessupporting
confidence: 79%
“…On the other hand, in contrast to the L 1 0 -MnGa and L 1 0 -MnAl films displaying the orbital 2CK effect2123, these L 2 1 -Co 2 MnAl films show a clear absence of a ln T dependence in the resistivity at higher energy scale, which further implies the inapplicability of 2CK explanation here. Here, we mention that our systematic study on Co 2 MnAl films with controlled disorder may also suggest a diffusion channel EEI mechanism for the low- T resistivity upturns in Heusler Co 2 Mn 0.25 Ti 0.75 Al20, Co 2 MnSi28, and Co 2 MnGa films29, while the weak localization explanation in the literature seems problematic.…”
Section: Resultsmentioning
confidence: 70%
“…Structural disorder such as impurities, strain, and dislocations in Mn-based alloys has been proved to account for the large variations in magnetooptical Kerr effects1516, Gilbert damping17, magnetic anisotropy18, anomalous Hall effect19, and for the occurrence of electronic disorder physics (e.g. weak localization20 and atomic tunneling effects212223). However, so far, the disorder effects on the transport properties of Co 2 MnAl films have been barely investigated.…”
mentioning
confidence: 99%
“…The presence of a resistivity minimum has been reported in the literature for similar materials. [22][23][24] Both the resistivity minimum and the cross over from metallic to semiconducting resistivity can find a consistent explanation in the theory of conduction in disordered three dimensional systems, in particular Kaveh and Mott's generalization 25 of Mooij criterion. 26 It has been suggested that the crossover from metallic to nonmetallic conduction, due to localization effects, should occur at low enough temperatures for all disordered cases (irrespective of specific value of the residual resistivity).…”
Section: Figures 4(b)-4(d)mentioning
confidence: 69%
“…However, similarly small effects on such films have been reported earlier. 18,[22][23][24] Before discussing our analysis of this data using different models, we note that the effects of electron-phonon scattering have been ignored.…”
Section: B Transport Measurementmentioning
confidence: 99%